FR 50% in pregnancy results in different neuron and glial cell count (astrocytes, olygodendrocytes, and microglia) in the cerebrum and cerebellum of newborn Rattus norvegicus - Fitria Desky; Hermanto Tri Joewono; Widjiati Widjiati (Universitas Airlangga, 2019)
Objectives: To analyze the difference neuronal and glial (astrocytes, oligodendrocyte, microglia) cell count in cerebrum and cerebellum of Rattus norvegicus newborns with 50% food restriction and control group.Materials and Methods: This was an analytical experimental study with single blind randomized post test only control group design using animals subjects Rattus norvegicus. This study was conducted at Animal laboratory, Veterinary Faculty, Universitas Airlangga. Animal subjects were divided into FR50% group and control. Neuron and glial (astrocytes, oligodendrocytes, microglia) counts were analyzed using comparison test, with CI 95%.Results: There was a significant difference in cerebrum and cerebellum neuron cell count between intervention and control group (9.88+3.59 vs 16.88+2.553; p=0.000 and 7.5+1.789 vs 11.44+4.56; p=0.02). There was no difference in cerebrum and cerebellum glial cell count. There was a significant difference in cerebellum astrocyte between intervention and control group (80.94+24.255 vs 59.69+18.77; p=0.02) but no difference in cerebrum. There was a significant difference in cerebrum and cerebellum oligodendrocyte between intervention and control group (14.06+12.195 vs 25.13+8.609; p<0.000 and 13.63+6.712 vs 24.00+8.862; p=0.001), and there were significant difference in cerebrum and cerebellum microglia cell between intervention and control group (5.25+3.435 vs 4.94+3.838; p=0.620 and 8.81+4.119 vs 5.25+1.483; p=0.004).Conclusion: Food Restriction 50% (FR50%) in Rattus norvegicus decreased cerebrum and cerebellum neuron cell and oligodendrocyte count and increased cerebrum and cerebellum microglial count.